Hubungan Teman Sebaya terhadap Pengetahuan dan Sikap Remaja Dalam Pencegahan HIV/AIDS di SMA Raksana Medan - Deviana Pratiwi Munthe (Malahayati Nursing Journal, 2022)
ABSTRACT HIV/ AIDS cases have increased significantly, especially among adolescents, due to the current development of globalization. Based on data from the Ministry of Health in 2015, there were 3.6% of new HIV cases among adolescents (2.030 people). This problem by the lack of knowledge and attitudes of young people about the prevention of HIV/ AIDS transmission. To determine the relationship between peer groups and the knowledge and attitudes of adolescents about preventing the transmission of HIV/ AIDS infection. This was an analytical survey study using a cross-sectional study. The population in this research was 406 people consisting of students of class X and XI where 143 people were samples. Sampling was using a simple random sampling technique. Collected data by distributing questionnaires and analyzed by using the Chi-square test. There was a significant relationship among peer groups, knowledge, and attitudes of adolescents about preventing HIV/ AIDS infection where the p-value was 0.005, there was significant relationship among peer group and knowledge of adolescents about preventing HIV/ AIDS transmission at p-value 0.029, and there was a significant relationship among peer groups towards adolescent attitudes about preventing HIV/ AIDS transmission at p-value 0.017. Peer groups have a significant relationship with adolescent knowledge and attitudes in preventing HIV/ AIDS transmission. Keywords: peer groups, knowledge, attitudes, preventing HIV/ AIDS   ABSTRAK Kasus HIV/ AIDS meningkat tajam terutama pada remaja tidak terlepas dari perkembangan globalisasi saat ini. Berdasarkan data Kementerian Kesehatan pada tahun 2015 terdapat 3,6% kasus baru HIV pada remaja (2.030 orang). Hal ini disebabkan kurangnya pengetahuan dan sikap remaja tentang pencegahan penularan HIV/ AIDS. Untuk mengetahui hubungan kelompok teman sebaya terhadap pengetahuan dan sikap remaja tentang mencegah penularan infeksi HIV/ AIDS. Penelitian survei analitik dengan menggunakan studi cross sectional. Populasi dalam penelitian sebanyak 406 orang terdiri dari siswa kelas X dan XI dimana 143 orang adalah sampel, Pengambilan sampel menggunakan teknik simple random sampling. Pengumpulan data dengan mendistribusikan kuesioner dan dianalisis dengan uji Chi square. Ada hubungan yang signifikan antara kelompok teman sebaya dengan pengetahuan dan sikap remaja tentang mencegah infeksi HIV/ AIDS dimana p-value 0,005, ada hubungan yang signifikan antara kelompok teman sebaya terhadap pengetahuan remaja tentang mencegah penularan HIV/ AIDS pada p-value 0,029 dan ada hubungan yang signifikan antara kelompok teman sebaya terhadap sikap remaja tentang mencegah penularan HIV/ AIDS pada p-value 0,017. Kelompok teman sebaya berhubungan secara signifikan dengan pengetahuan dan sikap remaja dalam pencegahan penularan HIV/ AIDS. Kata kunci: teman sebaya, pengetahuan, sikap, pencegahan HIV/ AIDS